Optimization of the kinematic mode of operation of the tractor-driven tillage tool - Saveliev Yuri (EDP Sciences, 2021)
A traction-driven tillage tool with low traction resistance has been developed. A decrease in the tractive resistance of the implement is achieved by transferring the main share of the power consumed by the implement to the process of loosening the soil through the tractor power take-off shaft (PTO) to the drive needle discs, which in turn create a pushing force. The efficiency of the technological process of soil cultivation depends on the kinematic mode of operation of each row of disk working bodies of the tractiondrive tillage implements. To optimize their kinematic mode of operation, a multifactorial experiment was carried out, which made it possible to establish the optimal values of such factors as the kinematic parameters of the 1st and 2nd rows of needle disks at the set operating speed of the unit.